THE BUSINESS ANALYSIS TILAPIA CULTIVATIFION (oreochromisniloticus) IN POND AT TEBING TINGGI VILAGE BENAI SUB DISTRICT KUANTAN SINGINGI REGENCY RIAU PROVINCE - Januarika '; Hendrik '; Hamdi Hamid (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This research is purpose to detemine the amount of invesment, income, profit also feasibility of tilapia cultivation in the pond in Tebing Tinggi Village, district of Benai, Regency of Kuantan Singingi. The method used based on case study. Populations in this research are 11 firsh farmers. From that populations sample taken with Stratified Random Sampling. Stratified Random Sampling is a method to choose sample by dividing populations into three categories that called level that is small secondary and big scale.Result ofresearch showed average investment of small scale that is Rp. 13.672.063. secondary scale that is Rp. 33.059.550 and for big scale it shown Rp. 116.571.950. Small scale earns Rp. 10.242.000 for average income and benefits about Rp. 1.783.388,-/hervest. Secondary scale aerns Rp. 27.166.000 and benefits about Rp. 6.158.182,-/harvest. Foe the big scale result shown Rp. 100.674.000 for average income and benefits Rp. 22. 947.184,-/harvest. Value of average RCR obtained from the small scale is 1,21, and 1,29 for secondary scale and 1,30 for big scale. Average FRR for small scale is 13,04%. 18,63% for secondary scale and 19,68% for the big one. And the value of average PPC for all scale are 5,67 period (small) 5,37 period (secondary) 5,08 period (big).Keywords : Tilapia, Investment, Income, Benefit, RCR, FRR, PPC